Novel Approaches and Cognitive Neuroscience Perspectives on False Memory and Deception - Toglia, Michael P.; Schmuller, Joseph; Surprenant, Britni G.; Hooper, Katherine C.; DeMeo, Natasha N.; Wallace, Brett L. (Frontiers in Psychology, 2022)
The DRM (Deese-Roediger-McDermott) paradigm produces robust false memories of non-presented critical words. After studying a thematic word list (e.g., bed, rest, pillow) participants falsely remember the critical item “sleep.” We report two false memory experiments. Study One introduces a novel use of the lexical decision task (LDT) to prime critical words. Participants see two letter-strings and make timed responses indicating whether they are both words. The word pairs Night-Bed and Dream-Thweeb both prime “sleep” but only one pair contains two words. Participants were as likely to recognize critical words (false memories) and presented words (true memories) just as when studying thematic lists. Study Two extends these findings by using functional near-infrared spectroscopy (fNIRS) to measure activity in the prefrontal cortex during a traditional DRM task which includes a deception phase where participants intentionally lie about critical lures. False and true memories occurred at high levels and activated many of the same brain regions but, compared to true memories, cortical activity was higher for false memories and lies. Accuracy findings are accompanied by confidence and reaction time results. Both investigations suggest that it is difficult to distinguish accurate from inaccurate memories. Results are explained in terms of activation-monitoring theory and fuzzy trace theory. We provide real world implications and suggest extending the present research to varying age groups and special populations. A nagging question has not been satisfactorily answered: could there be neural pathways that signal the presence of false memories and lies? Answering this will require imaging experiments which concentrate on regions of distinction such as the anterior prefrontal cortex.